Inhibition of PP2A in a mono and co-culture model of hepatocelluar carcinoma : implications on the regulation of the matrix metalloproteinase system and the formation of the metastatic niche - Ward, Mark (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Pharmacology & Therapeutics, 2016)
Okadaic acid alteration in Hep3B cells Phosphoproteome: Cell proliferation was measured by MTT assay. Okadaic acid (OA; 40 nM) increased HepSB cells cell proliferation after 12, 24 and 48 h compared to untreated control (P<0.05). Migration and angiogenesis assay were assessed using scratch and HUVEC tube formation assays following exposure to OA (40 nM). OA increased HepSB cell migration by 43.7 ± 4.3% compared to untreated control (P<0.05), while FTY-720+OA reduced cell invasion compared to OA alone by 18.7 ± 4.9% (P<0.05). OA increased HUVEC tube formation ability while FTY-720 and FTY 720+OA impaired it. Phosphoprotein enrichment and resulting mass spectrometry analysis identified 281 basal phosphoiylated proteins in HepSB cells, while a further 180 proteins were identified following exposure to OA (40 nM). Cellular process (00:0009987), metabolic process (00:0008152) and cellular organisation (00:0016043) were the major ontologies of the OA phosphoiylated proteins identified using PANTHER gene ontology.
Keywords: Pharmacology and Therapeutics, Ph.D.; PhD Trinity College Dublin, 2016